Unusual metastases of lung cancer: bulbus oculi and maxillary sinus - Ates, I.; Yazici, O.; Ates, H.; Ozdemir, N.; Zengin, N. (Experimental Oncology, 2015)
Lung adenocarcinoma often makes metastasis to the brain, liver, kidneys, bone, bone marrow and adrenal glands. It can also make metastasis to other parts of the body rarely for example eye, nose, parotid gland and paranasal sinus. We did not encounter with combined ocular bulbus and the maxillary sinus metastases of lung cancer in the accessible literature. In this case report, a patient who was combined ocular bulbus and the maxillary sinus metastases of lung adenocarcinoma will be discussed. Key Words: eye metastases, lung adenocarcinoma, paranasal sinus metastases.